VILLAGE TOURISM DEVELOPMENT WITH SHARING GRANTS MODEL THE SOLUTION TO PROMOTE VILLAGE SOVEREIGNTY - Wahyu Gunawan; Desi Yunita (Prodi Sosiologi FISIP Universitas Teuku Umar, 2015)
One of development strategyin an effort to encourage ruraleconomic growth is to make it as a tourist village, especially for villageswhich have valuable in tourism potential. In accelerate the development of a village into a tourism village it desperately needed the cooperation and support of many parties, because it pertains to the resources needed in that development. One of the concepts developed are sharing grants.That is a concept to encourage as many parties that have to be involved to develop the idea of understanding the village with herding resources owned by the parties.So that all the stakeholders involved will jointly engage independen tly. The purpose of development of rural tourism with the concept of sharing grants is to encourage the community to be involved in accordance with their desire and ability, so that the existence of these stakeholders will be an umbrella which can be placed the society. To make the changes beneficial in the implementation, it is necessary to make a guideline that would be the corridor of the village tourism development.